Insights of Pressure‐induced Unfolding of β‐Lactoglobulin as Revealed by Steered Molecular Dynamics. Issue 6 (28th March 2019) - Zhang, Zhuo; Hu, Hao; Xu, Xiaoyun; Pan, Siyi; Peng, Bangzhu
Abstract: High hydrostatic pressure (HHP) has been widely used in various industries, and the protein as one of the most noticeable bio‐macromolecules has exhibited distinct structural and functional characteristics under HHP conditions. In this work, steered molecular dynamics (SMD) simulations of β‐lactoglobulin (βlg) are exploited to investigate the flexibility of the individual secondary structural element of the polypeptide. The two loops and the two helices on the two sides of the molecular β‐barrel are found to be highly flexible and migrate toward the hydrophobic interior of the protein at relatively low pressures. Interestingly, there is evidence illustrating that water penetrations only occur from the loop‐side of the barrel under pressurizations, which is favored by the enlarged β‐barrel induced through the loop compression. Moreover, increased stability of βlg is attributed to the rigid regions of the protein molecule. N‐ and C‐termini of the polypeptide chain are also found to be of great importance to pressure‐induced unfolding of βlg. It is found the modeling results agree with previous experimental observations, demonstrating the validity of the applications of SMD for studies on pressure‐induced protein unfolding. Such methodology will provide new insight into HHP and be generalized for more complicated systems such as enzymes. Abstract : Steered and conventional molecular dynamics simulations are sequentially performed on a β‐lactoglobulin molecule and two loops on one side of the β‐barrel are flexible and sensitive to high pressure. Water molecules tend to enter into the β‐barrel only from the loop side during pressure‐induced unfolding of the β‐lactoglobulin.